Solid waste collection and willingness to pay for better service in Tema, Ghana - Akafia, Dzienyo Akutor (2014)
A thesis submitted to the Department of Theoretical and Applied Biology, Kwame Nkrumah University of Science and Technology, Kumasi in partial in partial fulfilment of the requirements for the award of Msc Degree in Environmental Science